1990
DOI: 10.1007/bf01331358
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of skim milk gels at various temperatures; interrelation between the dynamic moduli and the relaxation modulus

Abstract: A b s t r a c # The rheological properties of rennet-induced skim milk gels were determined by two methods, i.e., via stress relaxation and dynamic tests. The stress relaxation modulus Gc(t ) was calculated from the dynamic moduli G' and G" by using a simple approximation formula and by means of a more complex procedure, via calculation of the relaxation spectrum. Either calculation method gave the same results for Go(t). The magnitude of the relaxation modulus obtained from the stress relaxation experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
3
12
0
Order By: Relevance
“…He found that increasing the protein content of the base milk resulted in a less viscous product and that inclusion of a ropy strain had no effect on viscosity; however, he did find culture differences which may suggest different effects due to different EPS. This was supported by Zoon et al . (1990) , where data pointed to the existence of a permanent network where protein strand formation and protein–protein bond development is partially prevented by the presence of polysaccharide.…”
Section: Introductionsupporting
confidence: 79%
“…He found that increasing the protein content of the base milk resulted in a less viscous product and that inclusion of a ropy strain had no effect on viscosity; however, he did find culture differences which may suggest different effects due to different EPS. This was supported by Zoon et al . (1990) , where data pointed to the existence of a permanent network where protein strand formation and protein–protein bond development is partially prevented by the presence of polysaccharide.…”
Section: Introductionsupporting
confidence: 79%
“…Consequently, the calculated storage moduli would be lower than those shown. However, other factors (e.g., time scale of the tests and inherent variation in samples) can also affect agreement (Zoon, 1988;Zoon et al, 1990). For our data, the calculated storage modulus differed, in the worst case, by 30% from the measured one.…”
Section: The Storage (G') and Loss (G"mentioning
confidence: 61%
“…The computational verification of rheological data generally has not been reported. Zoon et al (1990) stated that if the same rheological property could be calculated from different types of experiments, it could provide a strong indication that true material properties had been measured. Accordingly, they calculated the shear relaxation modulus of skim milk gels from dynamic moduli data, and reported good agreement between calculated and measured values.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Higher values of elastic and viscous modulus in fresh cheese are believed to be due to these cross linkages and strong proteinprotein interactions. [28] Tunick et al [6] observed significant decrease in values of G 0 (from 55.2 to 42.2 kPa) and G 00 (from 19.9 to 14.6 kPa) in Mozzarella cheese upon refrigerated storage of 6 weeks. 3).…”
Section: Effect Of Storage On Viscoelasticitymentioning
confidence: 99%